2013
DOI: 10.1074/mcp.m112.025478
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of the Proteome in Primary Human Keratinocytes With Respect to Gender, Age, and Skin Localization

Abstract: Keratinocytes account for 95% of all cells of the epidermis, the stratified squamous epithelium forming the outer layer of the skin, in which a significant number of skin diseases takes root. Immortalized keratinocyte cell lines are often used as research model systems providing standardized, reproducible, and homogenous biological material. Apart from that, primary human keratinocytes are frequently used for medical studies because the skin provides an important route for drug administration and is readily ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 75 publications
(86 reference statements)
2
29
0
Order By: Relevance
“…In order to test also the keratinocyte signature, we searched for literature describing skin proteome profiles, which is rather scarce. However, Sprenger et al have presented an analysis of primary human keratinocytes listing more than 4000 proteins , which is also compatible with our signatures as it contains three members of our keratinocyte signature. Unexpectedly, the other three keratinocyte signature members, which are related to typical keratinocyte functions, are missing in this study.…”
Section: Resultssupporting
confidence: 88%
“…In order to test also the keratinocyte signature, we searched for literature describing skin proteome profiles, which is rather scarce. However, Sprenger et al have presented an analysis of primary human keratinocytes listing more than 4000 proteins , which is also compatible with our signatures as it contains three members of our keratinocyte signature. Unexpectedly, the other three keratinocyte signature members, which are related to typical keratinocyte functions, are missing in this study.…”
Section: Resultssupporting
confidence: 88%
“…However, there are also distinct BP GO terms associated with EV parental cell origin. These disparities may arise from the specific differences in the physiological conditions between the HaCaT cell line, which resemble transformed keratinocytes, and primary keratinocyte cells, that while more biologically relevant exhibit heterogeneity between donors [30,31]. Both the experimental and bioinformatic data indicated that fibroblast migration may be regulated by PKC-derived EVs but not by HaCaT-derived EVs, which demonstrates the association of biological processes with EV cellular origin.…”
Section: Discussionmentioning
confidence: 95%
“…Across all samples in this pilot experiment, 2412 proteins were identified at a 1% FDR, with nearly complete coverage of unfractionated results in the fractionated samples (Figure 1C). Despite analyzing only six samples in this test set, this number of protein identifications in a skin-related system is rivaled only by studies on undifferentiated primary keratinocytes or cell lines [12]. …”
Section: Resultsmentioning
confidence: 99%
“…To overcome this issue, past efforts have frequently employed separation of proteins via gel electrophoresis [810], a procedure with low throughput as well as poor sensitivity for lower abundance proteins [11]. Several published studies have been carried out using relatively undifferentiated cultured cells which do not suffer from such extreme dynamic range [1215]. Such studies can produce a large number of protein identifications but do not accurately represent the stratified structure and resulting protein profile of natural epidermis.…”
Section: Introductionmentioning
confidence: 99%